2020
DOI: 10.1371/journal.pbio.3000862
|View full text |Cite
|
Sign up to set email alerts
|

Many, but not all, lineage-specific genes can be explained by homology detection failure

Abstract: Genes for which homologs can be detected only in a limited group of evolutionarily related species, called “lineage-specific genes,” are pervasive: Essentially every lineage has them, and they often comprise a sizable fraction of the group’s total genes. Lineage-specific genes are often interpreted as “novel” genes, representing genetic novelty born anew within that lineage. Here, we develop a simple method to test an alternative null hypothesis: that lineage-specific genes do have homologs outside of the line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
202
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(217 citation statements)
references
References 58 publications
4
202
1
Order By: Relevance
“…A recent analysis exploited synteny to find that most taxonomically restricted genes are not the product of divergence, but have instead emerged de novo (Vakirlis, Carvunis, and Mclysaght 2019). Another recent study excluded genes with insufficient power to detect ancient homology, and similarly found that evidence for de novo origin persisted in a substantial number of cases (Weisman, Murray, and Eddy 2020). To get correct trends given random failures in homology detection, all we need is for apparent ages to be correlated with true ages.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis exploited synteny to find that most taxonomically restricted genes are not the product of divergence, but have instead emerged de novo (Vakirlis, Carvunis, and Mclysaght 2019). Another recent study excluded genes with insufficient power to detect ancient homology, and similarly found that evidence for de novo origin persisted in a substantial number of cases (Weisman, Murray, and Eddy 2020). To get correct trends given random failures in homology detection, all we need is for apparent ages to be correlated with true ages.…”
Section: Discussionmentioning
confidence: 99%
“…Since their initial discovery more than a decade ago [7,55,8], de novo genes and the mechanisms underlying their emergence have been studied intensely. However, concerns regarding the reliability of their computational identification [56,57,58], and if and how they code for functional proteins, have also been raised. We showed previously [30] that Gdrd is likely a de novo evolved gene, supported by its absence from the syntenic regions of outgroup species, the lack of detectably similar proteins in any other taxa, its intronic location, and its high level of intrinsic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Orthology inference relies on an initial similarity search to identify, among all pairs of genes in two organisms, those that are sufficiently similar to be potentially homologous ( Altenhoff et al, 2019 ). This step can be difficult if two orthologs have diverged significantly ( Jain et al., 2019 ; Weisman et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… Moyers and Zhang (2014 , 2017) have, like us, used simulation of gene evolution followed by a phylostratigraphic analysis and showed that faster evolving genes appeared younger than they should—i.e that orthologs of faster genes are less likely to be detected in more distant relatives. Recently, Weisman et al. (2020) showed that supposedly lineage-specific genes within the Drosophila and Saccharomyces genera have undetected homologs outside their respective lineages.…”
Section: Introductionmentioning
confidence: 99%